PENGARUH MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISWA PADA TEMA DAERAH TEMPAT TINGGALKU - Charianti Saragih; Reflina Sinaga; Saud Maulahe; Darinda Sofia Tanjung (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research aimed to analyze the effect of discovery learning model on students’ learning outcomes on the theme of “Daerah Tempat Tinggalku” at grade IV SD Negeri 091363 Huta Tinggir in academic year 2019/2020. The population was all fourth grade students totaling 50 students. Samples were taken by saturated sampling for as many as 50 students who were divided into two groups and each group consisted of 26 and 24 students. The method used in this research was experimental method in order to find out the effect of certain treatments on others conditions. The instrument in this research was